2022
DOI: 10.1002/slct.202103525
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Synthesis of Fused Chromeno‐Quinoline Heterocycles under Transition Metal‐Free Condition

Abstract: Among the various other organic compounds, the compounds having heterocyclic core are extensively circulated in nature and are often crucial for life. The concerned heterocyle may or may not be aromatic. They often show a variety of physiological, industrial and also theoretical significance. Quinoline derivatives are very popular anti-biotics and benzopyran or chromenes is another important heterocyclic moiety found widely in naturally occurring plant products like fruits and vegetables. However, when chromen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…66,67 Among the members of this family, fused benzo 4H-pyrans like 4H-chromene derivatives have been well-known because they are extensively present in nature including plants, vegetables, and fruits. 68 In 2020, Kamalzare and colleagues introduced a novel starch composite for the synthesis of the 4H-pyran derivatives (Scheme 6). 69 They prepared CuFe 2 O 4 -starch as a magnetically recyclable nanocatalyst and used it to facilitate a three-component reaction between aldehydes, malononitrile, and dimedone or ethyl acetoacetate (as C-H activated acidic compounds).…”
Section: Magnetic Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…66,67 Among the members of this family, fused benzo 4H-pyrans like 4H-chromene derivatives have been well-known because they are extensively present in nature including plants, vegetables, and fruits. 68 In 2020, Kamalzare and colleagues introduced a novel starch composite for the synthesis of the 4H-pyran derivatives (Scheme 6). 69 They prepared CuFe 2 O 4 -starch as a magnetically recyclable nanocatalyst and used it to facilitate a three-component reaction between aldehydes, malononitrile, and dimedone or ethyl acetoacetate (as C-H activated acidic compounds).…”
Section: Magnetic Starchmentioning
confidence: 99%
“…However, the literature review shows that chromenoquinoline compounds that contain both these units at their structure have many interesting properties. 68 For example, some of these compounds have shown the ability to act like fluorescence sensors. 101 Recently, Sayahi et al reported a sulfonic acid functionalized magnetic starch as a novel and efficient catalyst for the synthesis of chromeno[4,3- b ]quinoline-6,8(9 H )-dione derivatives (Scheme 21).…”
Section: Starch As Catalyst For Organic Reactionsmentioning
confidence: 99%